Antiferromagnetic CuMnAs multi-level memory cell with microelectronic compatibility - Olejnik, K.; Schuler, V.; Marti, X.; Novák, V.; Kaspar, Z.; Wadley, P.; Campion, R.P.; Edmonds, K.W.; Gallagher, B.L.; Garces, J.; Baumgartner, M.; Gambardella, P.; et al. (Nature Publishing Group, 2017)
Antiferromagnets offer a unique combination of properties including the radiation and magnetic field hardness, the absence of stray magnetic fields, and the spin-dynamics frequency scale in terahertz. Recent experiments have demonstrated that relativistic spin-orbit torques can provide the means for an efficient electric control of antiferromagnetic moments. Here we show that elementary-shape memory cells fabricated from a single-layer antiferromagnet CuMnAs deposited on a III–V or Si substrate have deterministic multi-level switching characteristics. They allow for counting and recording thousands of input pulses and responding to pulses of lengths downscaled to hundreds of picoseconds. To demonstrate the compatibility with common microelectronic circuitry, we implemented the antiferromagnetic bit cell in a standard printed circuit board managed and powered at ambient conditions by a computer via a USB interface. Our results open a path towards specialized embedded memory-logic applications and ultra-fast components based on antiferromagnets.